2022
DOI: 10.3390/e24030408
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Method Using HAVOK Analysis and Machine Learning for Predicting Chaotic Time Series

Abstract: The prediction of chaotic time series systems has remained a challenging problem in recent decades. A hybrid method using Hankel Alternative View Of Koopman (HAVOK) analysis and machine learning (HAVOK-ML) is developed to predict chaotic time series. HAVOK-ML simulates the time series by reconstructing a closed linear model so as to achieve the purpose of prediction. It decomposes chaotic dynamics into intermittently forced linear systems by HAVOK analysis and estimates the external intermittently forcing term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The above researches have shown that the detection performance of weak pulse signals depends on the accuracy of chaotic signal prediction. The higher prediction accuracy, the better detection performance of the model [11]. Recently, methods such as fractional maximum correlation entropy algorithm, deep learning and extreme learning machine have been used to the prediction of chaotic time series [12][13][14], which significantly improves the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The above researches have shown that the detection performance of weak pulse signals depends on the accuracy of chaotic signal prediction. The higher prediction accuracy, the better detection performance of the model [11]. Recently, methods such as fractional maximum correlation entropy algorithm, deep learning and extreme learning machine have been used to the prediction of chaotic time series [12][13][14], which significantly improves the prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Karimov et al constructed a chaotic circuit from data to identify chaos systems [14]. Yang et al introduced the Hankel Alternative View of Koopman analysis to decompose chaotic dynamics into a linear model with intermittent forcing [15]. The most widely used methods of chaotic time series analysis are neural network-related methods, which are classified into artificial neural networks (ANN) [16][17][18][19][20], fuzzy neural networks (FNN) [21][22][23][24], optimization algorithms with ANN [25][26][27][28], and wavelet neural networks (WNN) [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning has accomplished extraordinary triumphs in the avenue of computer vision [1], semantic segmentation [2], regression prediction [3], natural language processing [4], etc. However, two problems of traditional machine learning are gradually exposed: Firstly, traditional machine learning requires a large amount of labeled data, and the cost of collecting and labeling data is expensive; thus, it is difficult to be applied in fields that lack the data required for training models.…”
Section: Introductionmentioning
confidence: 99%